LncRNA FENDRR/ miR-424-5p serves as a diagnostic biomarker for sepsis and its predictive value for clinical outcomes - Xue Luo; Xin Chen; Ying Gu; Honggang Jia; Xinyu Lin; Ling Wang; Jingyun Feng (Immunobiology)
Purpose: This study intends to investigate the relationship between FENDRR and miR-424-5p and their clinical significance in sepsis, aiming to provide new diagnostic markers and prognostic markers for sepsis. Methods: 136 patients with sepsis and 132 healthy volunteers were included as study subjects. The expression levels of FENDRR and miR-424-5p were detected by qPCR. ROC was applied to evaluate the diagnostic value of FENDRR and miR-424-5p. COX analyzed the independent risk factors for the occurrence of death in sepsis patients. Dual luciferase reporter assay detected the binding of FENDRR and miR-424-5p. The miR-424-5p target genes were predicted and enriched for GO function and KEGG pathway. Results: FENDRR was up-regulated and miR-424-5p was down-regulated in patients with sepsis. FENDRR can target and bind to miR-424-5p. Both FENDRR and miR-424-5p showed significant diagnostic potential in sepsis and their combination significantly improved the diagnostic efficiency. FENDRR/miR-424-5p were significantly correlated with WBC, CRP, APACH II, and SOFA of sepsis patients. FENDRR and miR-424-5p were independent risk factors for mortality in sepsis patients. Sepsis patients with high FENDRR levels or low miR-424-5p levels had higher mortality. GO and KEGG enrichment analyses revealed that the targets of miR-424-5p were predominantly associated with cell functions and inflammatory signaling pathways. Conclusion: Upregulated FENDRR and downregulated miR-424-5p expression can serve as biomarkers of sepsis with predictive value on the onset and prognostic outcome. FENDRR and miR-424-5p were correlated with the severity of sepsis and FENDRR can play a function in the sepsis progression via targeting miR-424-5p.